PENINGKATAN PEMAHAMAN DALAM UPAYA PENCEGAHAN HIPERTENSI MELALUI INTERVENSI PENYULUHAN DI RT 04 DUKUH DRUWO, BANGUNHARJO, SEWON, BANTUL, YOGYAKARTA - Solikhah Solikhah; Prima Novita Putri; Ekha Rifki Fauzi (Randang Tana - Jurnal Pengabdian Masyarakat, 2023)
Hypertension is one of the causes of premature death and heart disease worldwide. Complications of hypertension can attack various organs of the body such as the heart (ischemic heart disease, left ventricular hypertrophy, heart failure), brain (stroke), kidneys (kidney failure), eyes (retinopathy), and peripheral arteries (intermittent claudication). Damage to these organs depends on the patient's high blood pressure and how long the high blood pressure is uncontrolled and untreated. Risk factors that cause hypertension can be influenced by unhealthy lifestyles such as lack of physical activity, stress factors, and the wrong diet. Modern food factors as a major contributor to the occurrence of hypertension in the community. Based on the 2013 Riskesdas results, the prevalence of hypertension in DIY was 25.7%. Based on the 2016 DIY health profile, the prevalence of hypertension in Bantul Regency is 26.12%. This community service is implemented through the dissemination of face-to-face education to the community on the subject of hypertension prevention. Throughout the execution of the activity, Pre-Test and Post-Test measurements were conducted. Thirty individuals in Dukuh Druwu were educated via poster medium. The average score for public comprehension of hypertension prevention increased by 20%. The increase in the average score is one of the evidences of the success of the extension. Then posters were installed at two points in RT 04, namely at the house of the cadre's mother and the mosque's wall magazine.